Improving Physical Competence of Elementary School Students through Traditional Game-Based Physical Activities - Sahabuddin, Sahabuddin; Ishak, Muhammad; Rahyuddin, Rahyuddin; Angriawan, Tri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2025)
This community service activity aims to improve students' physical competence through a traditional game-based physical activity approach. The target of the activity is 60 students in grades IV and V of SD Negeri 4 Mangkura, Makassar City. The activity is carried out in three stages: pre-activity (coordination and needs assessment), implementation (teacher training, parent counseling, and game practice), and post-activity (evaluation and dissemination). The five aspects of physical competence measured include endurance, agility, balance, leg muscle strength, and motor coordination. The measurement results showed a significant increase in all aspects, with an average pre-activity score of 58–65 increasing to 72–80 after the program was implemented. Qualitatively, there was an increase in active student participation, changes in behavior towards being more disciplined and cooperative, and increased awareness of teachers andparents regarding the importance of local culture-based physical activity. This program also succeeded in reviving interest in traditional games in the school environment. This community service proves that the PJOK learning model that integrates local cultural values through traditional games is able to improve physical competence while building student character. This activity is recommended to be expanded to other schools as part of strengthening character education and preserving culture.